Ordinary Language and Economic Language - Petrilli, Susan; Ponzio, Augusto (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2020)
We explore the language of economics from the perspective of the relation between signs, language and ideology. The focus is on social reproduction in global communication. From the epistemological viewpoint linguistics and economics are interrelated, both are sign sciences and value sciences. Saussure’s general linguistics is modelled on economics, particularly marginalist “pure economics” from the Lausanne school. In the 1960s Rossi-Landi reconsiders the relationship between linguistics and economics, specifically political economy in the Smith-Ricardian and Marxian tradition. In this context linguistic value is not limited to the market, the synchronic axis, and confused with price. Critical of both Saussure’s Cours de linguistique générale and of Wittgenstein’s interpretation of “meaning” as “use”, Rossi-Landi (1966, 1968) – who can be reread today in light of globalized communication as proposed by A. Ponzio (2008) – investigates the production processes of linguistic value applying the theory of labour-value, thus speaker “linguistic work” accumulated in fixed capital (language) from one generation to the next. Thematization of the relationship between linguistics and economics contributes to understanding the concepts of “sign fetishism” and “sign materiality,” while the theory of “language as work and trade” and of “ideology as social planning” throw light on the question of “social alienation”, which in the language of the sign sciences is also “linguistic alienation” and more generally “sign alienation”.